2012
DOI: 10.1099/jmm.0.042598-0
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin resistance and serotype distribution of Streptococcus pneumoniae in nasopharyngeal carrier children under 5 years of age in Dar es Salaam, Tanzania

Abstract: This study aimed to determine the magnitude of nasopharyngeal carriage, antimicrobial resistance and serotype distribution of Streptococcus pneumoniae in healthy children under 5 years of age in Tanzania. Nasopharyngeal swabs were obtained from 300 healthy children attending a child health clinic at Muhimbili National Hospital in Dar es Salaam, Tanzania. S. pneumoniae was isolated and identified using conventional methods. Antimicrobial susceptibility testing was performed using the Kirby-Bauer disc diffusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
30
10
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 45 publications
10
30
10
3
Order By: Relevance
“…This difference might be due to the age differences between our study subjects (≤6 years of age) and those of the previous study, which included children ≤13 years of age [18]. The overall carriage in our study was relatively low when compared with prevalence rates reported in other African countries; 22%-60% in Kenya [22,23], 62% in Uganda [24], 90% in Gambia [25] and 35% in Tanzania [26]. This may be due to the low numbers of children below the age of two years included in this study (Table 1).…”
Section: Discussionmentioning
confidence: 63%
“…This difference might be due to the age differences between our study subjects (≤6 years of age) and those of the previous study, which included children ≤13 years of age [18]. The overall carriage in our study was relatively low when compared with prevalence rates reported in other African countries; 22%-60% in Kenya [22,23], 62% in Uganda [24], 90% in Gambia [25] and 35% in Tanzania [26]. This may be due to the low numbers of children below the age of two years included in this study (Table 1).…”
Section: Discussionmentioning
confidence: 63%
“…In addition, NVT were acquired faster (median age at acquisition, 152 days vs. 174; p = 0.004) and had a shorter duration of carriage (median duration, 43 vs. 70 days; p<0.001) than PCV7-serotypes [50]. Between 36% and 56% of the pneumococcal isolates detected in unvaccinated healthy children <5 years of age in Africa were of PCV-7 serotypes [50], [51], [57], [63], [64], whereas the proportions were 37%–56% for PHiD-CV (10-valent pneumococcal Haemophilus influenzae protein D conjugate vaccine) and 50%–64% for PCV-13 (13-valent pneumococcal conjugate vaccine) [51], [63]. Non-typeable S. pneumoniae represented between 0.7% [55] and 20.6% [60] of the isolates.…”
Section: Resultsmentioning
confidence: 99%
“…The pooled prevalence for carriage o f S. pneumoniae in healthy children <5 years of age was 64.8% (95% CI, 49.8%–76.1%) for the five populations from low income countries [52], [53], [55], [63], [65] and 47.8% (95% CI, 44.7%–50.8%) for the six populations from lower-middle income countries (Figure 2) [36], [56], [66][69]. However, studies were highly heterogeneous in the low income countries (I 2  = 98%), in contrast to those in the lower-middle income countries (I 2  = 0%).…”
Section: Resultsmentioning
confidence: 99%
“…(Constenla, 2008). O uso de agentes antimicrobianos está entre as principais estratégias de combate as infecções pneumocócicas, porém a dificuldade em estabelecer um tratamento eficaz é devido ao surgimento de cepas resistentes a antibióticos, principalmente ß-lactâmicos (Kim et al, 2012;Moyo et al, 2012).…”
Section: Lista De Abreviaturas E Siglasunclassified